Sorting Things Out: Classification and Its Consequences - Elizabeth R. Lorbeer (Issues in Science and Technology Librarianship)
The article reviews the book Sorting Things Out: Classification and Its Consequences. Cambridge, MA: MIT Press, 1999. 377 pp. $ 29.95 (ISBN 0-262-02461-1), by Geoffrey C. Bowker and Susan Leigh Star.